A baseline study of an informal market economy among Dayak Women in Bau and Sri Aman districts - Chua, Amy Fang Lim (Faculty of Social Sciences, 2005)
This study attempts to examine empirical evidence on the participation of women in the informal economy sector in Bau and Sri Aman district. Two groups of Dayak women were involved in this study. The specific objectives were to determine the respondent's characteristic and their daily activities from selling vegetables in market.